BUAH MANGGIS SEBAGAI KONSEP PENCIPTAAN KARYA SENIGRAFIS - Drs. Irwan, M.Sn., Sandi Herman, Yofita Sandra, S.Pd., M.Pd., (Serupa The Journal of Art Education, 2016)
In minangkabau mangosteen is tightly by philosophy of tradition that is as a symbol of leader honesty. The purpose of this finally project if to visualitation mongosteen as symbol of leader honesty in art graphic. Live side that raised is unbalanced the honesty in the leadership.Creating process of this finally project is using method cerigraphy by broken cliche type. Every picture that created is connected each other bicause of the same theme, idea and concept. After through a long prosess the creator is making a finally project by the tittle: 1) Terlalu berat, 2) Terikat, 3) Politik, 4) Berbeda 5) Diujung senja 6) Billiard, 7) Tak terbawa, 8) Bimbang, 9) Tak berarti, 10) Meleleh. By creating grapics art is hopefully to the member of art development in order to increase the spirit in artwork and also can be reference to make a graphic art be better in future.Key: mangosteen, graphic art, cerigraphy.